x-7=6(5-6x)

Simple and best practice solution for x-7=6(5-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-7=6(5-6x) equation:


Simplifying
x + -7 = 6(5 + -6x)

Reorder the terms:
-7 + x = 6(5 + -6x)
-7 + x = (5 * 6 + -6x * 6)
-7 + x = (30 + -36x)

Solving
-7 + x = 30 + -36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36x' to each side of the equation.
-7 + x + 36x = 30 + -36x + 36x

Combine like terms: x + 36x = 37x
-7 + 37x = 30 + -36x + 36x

Combine like terms: -36x + 36x = 0
-7 + 37x = 30 + 0
-7 + 37x = 30

Add '7' to each side of the equation.
-7 + 7 + 37x = 30 + 7

Combine like terms: -7 + 7 = 0
0 + 37x = 30 + 7
37x = 30 + 7

Combine like terms: 30 + 7 = 37
37x = 37

Divide each side by '37'.
x = 1

Simplifying
x = 1

See similar equations:

| 25X-3=5(5X+9) | | a+8-5a+6+2a+9+4a-a=4a+7-2a+8-2a-10 | | (2w-7)(6-w)=0 | | 2n+4=-8-n+3n | | 0.8x-8=2x+4 | | 0.25x+2(x-2)=4x+1 | | 2x+x+3=8x-5x+3 | | -3x+5x+4=-5 | | 9+6q=10+59 | | 5v+4v+6= | | 55x+2295x-78=47(50x+34) | | 6p+7q=89 | | 3x=9x^2-10 | | 3Z/7-1=10 | | x*dx+(y-2)*dy=0 | | .95n=n+4 | | 5(3x+2)-(8x-4)=16-3 | | 285.9912=2*3.14*r^2+2*3.14*r*4 | | 4(X+1)=7X+2-3X+2 | | x+(-34)=2x+(-6) | | 27=2x+x | | 9x+2+32+3x=90 | | -(-x+4)+12=3x+(5-x) | | -7x^2+x+9=-6x | | 4xy(6x+8y)= | | 15x-7y=-49 | | 9(x-2)=63 | | 0=-5sin(t) | | 5x-18=6x-24 | | 23.2=7.2 | | F(x)=2x^3-9x^2+12x-5 | | a+4=-2a+3 |

Equations solver categories